Pengaruh Digital Marketing, Inovasi Produk dan Brand Image terhadap Keputusan Pembelian pada Coffee Shop Pabrik Lewo Surabaya - Shinta Nur Alfiyah; Siti Aminah (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Coffee is a happening trend in this era of globalization as evidenced by the increasing number of coffee shops that are easily found in various places. One of them is the Lewo Factory Coffee Shop (Lemah Jowo) which has a unique and distinctive feature by selling coffee drinks from coffee plantations in Indonesia. However, there are several factors that influence the decline in purchasing decisions, such as digital marketing, product innovation and brand image. This study aims to determine the effect of digital marketing, product innovation and brand image on purchasing decisions for Lewo Factory Coffee Shop. The sample of this research is the consumers of the Lewo Factory Coffee Shop. The sampling technique used is accidental sampling with 70 respondents obtained by distributing questionnaires through google form. The data obtain ed using descriptive analysis with the PLS (Partial Least Square) application. The results of this study prove that the influence of digital marketing, product innovation and brand image has a positive and significant influence on purchasing decisions at the Coffee Shop Factory Lewo Surabaya. Keywords: Brand Image, Digital Marketing, Product Innovation, Buying Decision.